Electrochemical Double-Layer Capacitor Containing Mixtures of Ionic Liquid, Lithium Salt, and Organic Solvent as an Electrolyte - Li, Xiangyuan; Li, Hao; Feng, Rui; He, Long; Lu, Hai (Frontiers in Materials, 2021)
A modified ionic liquid (IL)-based electrolyte with conventional carbonates as support solvent and lithium salt as additive was designed for high-voltage electrochemical double layer capacitor (EDLC). It is found that the employment of carbonate solvents obviously enhances the ionic conductivity and decreases the viscosity of the electrolyte, while the addition of lithium salt plays a key role in the stabilization of operating potential window and modification of passivation layer on the electrode. As a result, increased specific capacitance, improved cycle stability and rate capability are demonstrated in the EDLC with EMI-BF4/LiPF6/PC/DMC electrolyte at the upper voltage of 3V, in contrast to that with pure IL and IL/carbonate mixture. This study primarily stresses the combination effect of Li salt and organic solvent in the IL electrolyte system for constructing advanced 3 V-class EDLC with excellent overall performance.